Composition and processing activity of a semi-recombinant holo U7 snRNP - Bucholc, Katarzyna (Nucleic Acids Res, 2020)
In animal cells, replication-dependent histone pre-mRNAs are cleaved at the 3′ end by U7 snRNP consisting of two core components: a ∼60-nucleotide U7 snRNA and a ring of seven proteins, with Lsm10 and Lsm11 replacing the spliceosomal SmD1 and SmD2. Lsm11 interacts with FLASH and together they recruit the endonuclease CPSF73 and other polyadenylation factors, forming catalytically active holo U7 snRNP. Here, we assembled core U7 snRNP bound to FLASH from recombinant components and analyzed its appearance by electron microscopy and ability to support histone pre-mRNA processing in the presence of polyadenylation factors from nuclear extracts. We demonstrate that semi-recombinant holo U7 snRNP reconstituted in this manner has the same composition and functional properties as endogenous U7 snRNP, and accurately cleaves histone pre-mRNAs in a reconstituted in vitro processing reaction. We also demonstrate that the U7-specific Sm ring assembles efficiently in vitro on a spliceosomal Sm site but the engineered U7 snRNP is functionally impaired. This approach offers a unique opportunity to study the importance of various regions in the Sm proteins and U7 snRNA in 3′ end processing of histone pre-mRNAs.